Mobile media, participation culture and the digital vernacular: 24-hours.in and the democratization of documentary. Issue 1 (1st October 2013) - Vickers, Richard
This article discusses the convergence of media technologies, participation culture and the new vernacular of mobile device photography. The author and Lincoln School of Media colleague, James Field, are developing a participatory interactive documentary project entitled 24-hours.in (www.24-hours.in), exploring new opportunities for participation, collaboration and the potential democratization of documentary production. Utilizing user-generated video captured on mobile phones and smart devices, the project is participatory whereby the audience contributes documentary videos around the theme of 24 hours in a city or location. With reference to Džiga Vertov's seminal 1929 documentary film Man with a Movie Camera, the intention is for the videos to document the cities, the people that live there and their daily lives. The aim of the project is to have an open and collaborative platform to which anyone can contribute; for the audience as 'user-producers' to document their city or location, the people that live there and their daily lives. Building on Vertovian concepts, the project explores the potential the ubiquitous camera-phone 'eye' may offer for a unique and cumulative version of 'cinema-truth' to emerge. By exploring a model of participation we have moved away from the authorship of a single person towards mass authorship and a collaborative montage vision, and in doing so revisit Vertov's aspirations for the democratization not just of technology but also of creativity.